PROJECT-BASED LEARNING TO DEVELOP STUDENTS' ABILITY AND CREATIVITY IN WRITING NARRATIVE STORY - Eva Fitriani Syarifah; Raynesa Noor Emiliasari (Indonesian EFL Journal, 2019)
In English language teaching, project-based learning is not only able to optimize language skills but also other skills such as critical and creative thinking. This study tries to investigate the use of project-based learning to develop students’ abilities and creativity in writing narrative text and the students’ perception towards the implementation of project-based learning in writing course. This study employed a qualitative approach by involving second semester students who take writing course. The results of this study indicated that project-based learning can help the students to develop their ability and creativity in writing narrative text in several point including their understanding of the topic, their knowledge about narrative genre namely social function, structure of text, and language feature. In addition, the students also showed their creativity through creating their story line and designing the illustration of the story. Furthermore, the students gave positive views toward the implementation of project-based learning. They mentioned that they learned networking, collaborative learning, and team work through PBL. Thus, project-based learning can be one of alternative ways to teach writing in higher education.Keywords: narrative text; project based learning; student creativity; teaching writing; writing skills.